2015
DOI: 10.1080/01635581.2015.990568
|View full text |Cite
|
Sign up to set email alerts
|

MAPK Genes Interact with Diet and Lifestyle Factors to Alter Risk of Breast Cancer: The Breast Cancer Health Disparities Study

Abstract: Mitogen-activated protein kinases (MAPK) are integration points for multiple biochemical signals. We evaluated 13 MAPK genes with breast cancer risk and determined if diet and lifestyle factors mediated risk. Data from three population-based case-control studies conducted in Southwestern United States, California, and Mexico included 4183 controls and 3592 cases. Percent Indigenous American (IA) ancestry was determined from 104 Ancestry Informative Markers. The adaptive rank truncated product (ARTP) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
(56 reference statements)
2
16
0
Order By: Relevance
“…Some are relevant to NTDs, the indication for maternal folic acid supplementation, and others to distinct developmental conditions that have not been previously associated with maternal folate levels. Additional genes we identified have been implicated in conditions where there is some concern about possible adverse effects of higher folate levels, such as breast cancer progression 16 . Due to the large number of genes significantly differentially methylated in relation to folate ( Supplementary Data 1 and 2 ), we focus this discussion primarily on genes with two or more CpGs at genome-wide significance after FDR correction ( P BH <0.05) where at least one CpG is within the gene ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some are relevant to NTDs, the indication for maternal folic acid supplementation, and others to distinct developmental conditions that have not been previously associated with maternal folate levels. Additional genes we identified have been implicated in conditions where there is some concern about possible adverse effects of higher folate levels, such as breast cancer progression 16 . Due to the large number of genes significantly differentially methylated in relation to folate ( Supplementary Data 1 and 2 ), we focus this discussion primarily on genes with two or more CpGs at genome-wide significance after FDR correction ( P BH <0.05) where at least one CpG is within the gene ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [26] showed an interaction between MAPK1 genetic variants and obesity and related lifestyle factors on breast cancer. Consistent with the results of that study, we found that carriers of the genetic variant in MAPK1 rs2298432 had decreased breast cancer risk only in non-viscerally obese women, indicating that IGF/IR axis cellular pathway-related carcinogenesis in this variant intermingles with visceral adiposity.…”
Section: Discussionmentioning
confidence: 92%
“…The PI3K/Akt pathway leads to metabolic activity, including glucose uptake and decreased apoptosis, and the MAPK pathway leads to mitogenic activity [54]; both are main signaling cascades in controlling cellular process promoting carcinogenesis [55,56]. PIK3R1, AKT1/2, and MAPK1 genes are the key components of these pathways [26,55,[57][58][59], but the studies of their genetic variants in relation to cancer have been limited [12,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations